2022
DOI: 10.1007/s00284-022-03112-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Investigations Relationship Between Viral Infections and Multiple Sclerosis Pathogenesis

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease that affects the central nervous system (CNS). Compared to other types of self-limiting myelin disorders, MS compartmentalizes and maintains chronic inflammation in the CNS. Even though the exact cause of MS is unclear, it is assumed that genetic and environmental factors play an important role in susceptibility to this disease. The progression of MS is triggered by certain environmental factors, such as viral infections. The most important viruses that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 92 publications
(223 reference statements)
0
11
0
Order By: Relevance
“…A review of a total of 24,117 cases of incident RA (mean age 54.7 years; 18,688 [77.5%] women) found that respiratory viral infections in the population were associated with a higher incidence of RA over time, an effect peaking 6 or 7 weeks after infection [ 186 ]. The progression of multiple sclerosis (MS) is also triggered by certain environmental factors, including viral infections [ 187 ]. The most important viruses that affect MS risks are Epstein–Barr virus (EBV), human herpes virus 6 (HHV-6), human endogenous retrovirus (HERV), cytomegalovirus (CMV), and varicella zoster virus (VZV).…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of a total of 24,117 cases of incident RA (mean age 54.7 years; 18,688 [77.5%] women) found that respiratory viral infections in the population were associated with a higher incidence of RA over time, an effect peaking 6 or 7 weeks after infection [ 186 ]. The progression of multiple sclerosis (MS) is also triggered by certain environmental factors, including viral infections [ 187 ]. The most important viruses that affect MS risks are Epstein–Barr virus (EBV), human herpes virus 6 (HHV-6), human endogenous retrovirus (HERV), cytomegalovirus (CMV), and varicella zoster virus (VZV).…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…These viruses all have latent stages that allow them to escape immune detection and to reactivate after exposure to various stimuli. Furthermore, viral tropism for CNS and immune system cells is likely to explain their potentially damaging neuroinflammatory effects [ 187 ].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…This, together with the small IRRs, provides little evidence for an association of autoimmune disease with subsequent dementia development, especially after adjustment for infections. Autoimmune disease diagnosis may also be preceded by infections (multiple sclerosis is a recent example 32 ), thus explaining the overall change in estimates after adjustment for infections. The small effect sizes reported may reflect ascertainment bias because patients with autoimmune conditions probably receive more thorough medical follow-up, which could increase the likelihood of receiving a dementia diagnosis.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Viral infection has long been suspected to be the etiological factor of MS. Multiple viruses are considered to be the causative pathogen, including EBV, HHV‐6, CMV, VZV, and HERV‐W, among which EBV earned the most focus 42 . Early in the 1980s, cohort studies observed that MS patients had a higher prevalence and higher titers of anti‐EBV antibodies compared to the healthy population 43 .…”
Section: Ebv Antibodies As Driving Factors Of Multiple Sclerosismentioning
confidence: 99%